TEACHERS’ PSYCHOLOGICAL IMPACT TOWARDS THE IMPLEMENTATION OF LESSON STUDY IN SCHOOL - Faizah Che Mat Zi; Zanaton Hj Iksan (Universitas Muhammadiyah Semarang, 2021)
Lesson Study (LS) is a practice of the teachers that is origin from Japan which give the positive impact towards the quality of educators‟ professionalism. This innovation will encourage the teacher to work collaboratively in sharing of knowledge, experience as well as research throughout the teaching period. However, the culture of LS has not been widely implemented in Malaysia even though it has been established here since 2011. This is because, most of the teachers consider that this LS is an additional workload that causes emotional disturbance and also can cause stress among them. The purpose of this study was to look at the psychological impact on the implementation of LS in schools. The psychological impact is seen in terms of teachers‟ acceptance and its relationship with teachers‟ stress on the implementation of LS. This study used a survey method by using the questionnaire instrument. A total of 186 teachers who teach in sekolah menengah kebangsaan harian were selected to be the sample of the study. The data were analysed descriptively and inferentially using Statistical Package for the Social Sciences (SPSS) software. The findings of this study show that the level of teachers‟ acceptance towards the implementation of LS is high. However, the level of teachers‟ stress related to the implementation of LS is at a low level. While, there is a negative and very weak relationship between teachers‟ acceptance towards the implementation of LS with teachers‟ stress related to the implementation of LS. In conclusion, the teachers need to be given more effective exposure to the implementation of LS so that they can further improve the quality of teaching professionalism in the future.Keywords: Lesson Study, teacher professionalism, professional learning community (PLC), teachers‟ workload, teachers‟ psychology